2023
DOI: 10.3390/foods12213963
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Water-Soluble Squid Ink Melanin: Stability, Free Radical Scavenging, and Cd2+ Adsorption Abilities

Shuji Liu,
Xianwei Liu,
Xueqin Zhang
et al.

Abstract: Squid ink melanin can be efficiently extracted from the byproduct ink sac generated during squid processing. As a natural food colorant, it possesses inherent antioxidant properties and the capability to adsorb heavy metals. This study aims to investigate the solubility of water-soluble squid ink melanin (WSSM) obtained from the ink sac, as well as its stability under various conditions including temperature, pH, salt, sugar, potassium sorbate, metal ions, sodium benzoate, sodium sulfite (reducing agent), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Previous studies have been focused on elucidating the physiological functions of melanin, especially in the field of dermatology . From a resource perspective, the melanin concentrated in the ink sacs of cuttlefish and squid is easily recoverable natural melanin. , The catch of squid and octopus has been increasing yearly and hovering around 3 million tons for the past few years . Recent studies have also reported melanin production by bioprocesses using melanin-producing microorganisms such as fungi and bacteria and efficient methods for extracting melanin from animal hair. Thus, renewable melanin obtained from diverse biological resources can be regarded as a sustainable biomass resource.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have been focused on elucidating the physiological functions of melanin, especially in the field of dermatology . From a resource perspective, the melanin concentrated in the ink sacs of cuttlefish and squid is easily recoverable natural melanin. , The catch of squid and octopus has been increasing yearly and hovering around 3 million tons for the past few years . Recent studies have also reported melanin production by bioprocesses using melanin-producing microorganisms such as fungi and bacteria and efficient methods for extracting melanin from animal hair. Thus, renewable melanin obtained from diverse biological resources can be regarded as a sustainable biomass resource.…”
Section: Introductionmentioning
confidence: 99%
“…13 From a resource perspective, the melanin concentrated in the ink sacs of cuttlefish and squid is easily recoverable natural melanin. 14,15 The catch of squid and octopus has been increasing yearly and hovering around 3 million tons for the past few years. 16 Recent studies have also reported melanin production by bioprocesses using melaninproducing microorganisms such as fungi and bacteria 17−21 and efficient methods for extracting melanin from animal hair.…”
Section: ■ Introductionmentioning
confidence: 99%